How emotional intelligence affects inter-organizational relationships in megaprojects: the boundary spanning perspective - Cao, Tingting; Locatelli, Giorgio; Smith, Nigel; Zhang, Lianying (Journal of Civil Engineering and Management, 2025)
Boundary Spanners (BSs) substantially impact relationship development in megaprojects. Yet, previous research only focused on the emotional intelligence (EI) of single-level BSs, e.g., megaproject managers and decision-makers. By clustering BSs into higher-level BSs (HBSs) and middle-lower-level BSs (M&LBSs), this article aims to investigate how to enhance inter-organizational relationships through different-level BSs’ EI and boundary-spanning behaviors including ambassadors, coordination and information scanning behaviors. Data from 119 HBSs and 171 M&LBSs in 15 megaprojects were first collected with a questionnaire survey. 18 semi-structured interviews were then undertaken to give a deeper explanation to the underlying mechanism. The results show that HBSs’ EI is directly and positively associated with inter-organizational relationships. However, the benefit of M&LBSs’ EI in megaprojects can only be realized through the mediating effect of their boundary-spanning behaviors. HBSs’ EI is effective in improving external ambassadors’ activities. In contrast, M&LBSs’ EI is effective in improving information scanning. This study advanced EI and relationship study in megaprojects, stating the mechanism between these two variables varies for different-level boundary spanners.